Studi Fenomenologi Dramaturgi Roleplay Grand Theft Auto V - Shindu Aji Pramudya; Sidiq Setyawan (Jurnal Politikom Indonesiana, 2026)
This study aims to understand the experiences and meanings of players in playing roles in the Roleplay Game Grand Theft Auto V through a phenomenological study approach. The research method used is descriptive qualitative with data collection through in-depth interviews with GTA V Roleplay players who actively play various roles in the game. The results show that players consciously construct and manage role identities according to the characters they play, as well as verifying between in-game identities (in character) and out-of-game identities (out of character). Analysis using Erving Goffman's dramaturgy theory shows the division of front stage and back stage areas in roleplay interactions, where players strive to maintain consistency of roles, dialogue, and actions to create an immersive social reality. In addition, interactions between players are also influenced by community norms, cooperation, and conflict management that shape social dynamics in the virtual world. These findings indicate that roleplay in GTA V functions not only as entertainment, but also as a social space that allows players to express themselves, build relationships, and interpret social roles reflectively.